2017
DOI: 10.1186/s12906-017-1789-x
|View full text |Cite
|
Sign up to set email alerts
|

Dai-Huang-Fu-Zi-Tang alleviates pulmonary and intestinal injury with severe acute pancreatitis via regulating aquaporins in rats

Abstract: BackgroundDai-Huang-Fu-Zi-Tang (DHFZT) is a famous traditional Chinese prescription with intestinal obstruction, acute pancreatitis and cholecystalgia for thousands of years. Our previous work found that DHFZT could act against pulmonary and intestinal pathological injury in rats with severe acute pancreatitis (SAP). But the underlying mechanism has not been fully elucidated. The aim of present study was to investigate whether DHFZT could relieve pulmonary and intestinal injury by regulating aquaporins after S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 51 publications
4
17
0
Order By: Relevance
“…unknown regulation, = unaffected) Aquaporin Tissue Regulation during inflammation References AQP1 Immune cells ↑ In leukocytes and cell lines (THP-1) [ 8 , 9 ] Heart ↑ In cardiac cells [ 58 ] Lung ↓ In lung tissue after LPS [ 5 , 6 ] AQP2 Kidney ↓ In renal tissue after LPS [ 37 ] AQP3 Immune cells ↓ In leukocytes of septic patients [ 8 ] AQP4 Brain ↑ In brain and anterior pituitary gland [ 31 , 75 ] AQP5 Lung ↓ In lung tissue after LPS [ 65 ] Immune cells ↓ In THP-1 cells after LPS [ 9 ] AQP7 Immune cells ? Mouse resident peritoneal macrophages [ 76 ] AQP8 Liver ↓ In hepatic cells [ 11 ] Lung = In bronchial epithelial cells [ 61 ] AQP9 ...…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…unknown regulation, = unaffected) Aquaporin Tissue Regulation during inflammation References AQP1 Immune cells ↑ In leukocytes and cell lines (THP-1) [ 8 , 9 ] Heart ↑ In cardiac cells [ 58 ] Lung ↓ In lung tissue after LPS [ 5 , 6 ] AQP2 Kidney ↓ In renal tissue after LPS [ 37 ] AQP3 Immune cells ↓ In leukocytes of septic patients [ 8 ] AQP4 Brain ↑ In brain and anterior pituitary gland [ 31 , 75 ] AQP5 Lung ↓ In lung tissue after LPS [ 65 ] Immune cells ↓ In THP-1 cells after LPS [ 9 ] AQP7 Immune cells ? Mouse resident peritoneal macrophages [ 76 ] AQP8 Liver ↓ In hepatic cells [ 11 ] Lung = In bronchial epithelial cells [ 61 ] AQP9 ...…”
Section: Discussionmentioning
confidence: 99%
“…In lung mainly the aquaporins AQP1 and 5, 8 and to a lower extent AQP9 are expressed [ 60 ]. Here, Aqp1 is expressed in all vascular endothelial cells, Aqp5 in the alveolar type I cells and Aqp8 and Aqp9 can be found in the bronchial epithelial cells in lung [ 61 ] (Fig. 2 c).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…DHFZT was composed of three herbs including Radix et Rhizoma Rhei (DH), Radix Aconiti Lateralis Preparata (FZ), and Radix et Rhizoma sari (XX), and it was originally described in the Synopsis of Golden Chamber (Jin Kui Yao Lue), which was a treatise on febrile and miscellaneous diseases written by the outstanding physician Zhang Zhongjing in Han Dynasty. Our previous study revealed that DHFZT markedly alleviates intestinal injury with severe acute pancreatitis via regulating aquaporins in rats [ 15 ]. However, the effect of DHFZT on intestinal injury with severe acute pancreatitis via regulating MPTP has not yet been entirely clear.…”
Section: Introductionmentioning
confidence: 99%